The Investment Climate for the Informal Economy : A Case of Durban, South Africa - Lund, Francie; Skinner, Caroline (World Bank, 2012)
This investment climate of South Africa's informal economy is investigated with special focus on the regulatory environment (taxes and laws), institutions, services (training, financial services and insurance, access to markets), and access to infrastructure and protection from crime. Durban, South Africa's third largest city, is ahead of other cities in responding to the growth of informal work and has been proactive in seeking out ways of creatively supporting informal enterprises.